The Oxford handbook of women and the economy - Averett, Susan; Argys, Laura M.; Hoffman, Saul D., 1949- (New York : Oxford University Press, 2017)
The transformation of women's lives in the past century is among the most significant and far-reaching social and economic phenomena, affecting not only women, but also their partners and children. This Handbook provides the first comprehensive collection of essays that addresses these issues, using the powerful framework of economics. The essays are divided into three broad sections-marriage and fertility; the labor market; and special topics and policy issues. Separate and special attention is given to developed and developing economies, because the constraints women face and the key policy issues vary by level of development. While the primary focus is economics, where appropriate, the essays incorporate the newest interdisciplinary research about gender from biology and other disciplines.
Marriage and Marriage Markets / Shoshana Grossbard -- The Causes and Consequences of Increased Female Education and Labor Force Participation in Developing Countries / Rachel Heath, Seema Jayachandran -- The Gender Wage Gap in Developed Countries / Astrid Kunze -- Occupation and Gender / Patricia Cortes, Jessica Pan -- Women and Science, Technology, Engineering, and Mathematics (STEM): Are Differences in Education and Careers due to Stereotypes, Interests, or Family? / Shulamit Kahn, Donna Ginther -- Gender Differences in Behavioral Traits and Labor Market Outcomes / Olga Shurchkov, Catherine C. Eckel -- Biology and Gender in the Labor Market / Deborah A. Cobb-Clark -- Women, Work, and Family / Francine D. Blau, Anne E. Winkler -- Women and Leadership / Amalia R. Miller -- Taxes, Transfers, and Women's Labor Supply in the United States / Melanie Guldi, Lucie Schmidt -- Access and Use of Contraception and Its Effects on Women's Outcomes in the United States / Martha J. Bailey, Jason M. Lindo -- Marriage-Market Search and Sorting: Explanations and Evidence / Hani Mansour, Terra McKinnish -- Fertility Policy in Developed Countries / Leonard M. Lopoo, Kerri M. Raissian -- U.S. Child Care Policy and Economic Impacts / Jean Kimmel, Rachel Connelly -- Maternity and Family Leave Policy / Maya Rossin-Slater -- The Care Penalty and Gender Inequality / Nancy Folbre -- Women's Labor Market Status and Economic Development / Nidhiya Menon, Yana van der Meulen Rodgers -- Women and the Labor Market: A Feminist Perspective / Joyce P. Jacobsen -- Racial Differences in American Women's Labor Market Outcomes: A Long-Run View / William J. Collins, Michael Q. Moody -- Gender: A Historical Perspective / Paola Giuliano -- Understanding Differences in Mortality and Morbidity by Sex: The Role of Biological, Social, and Economic Factors / Barbara Schone -- Women and Migration / Francisca M. Antman -- Maternal Socioeconomic Status and the Well-Being of the Next Generation(s) / Kasey S. Buckles -- Women in the Workplace and Management Practices: Theory and Evidence / Takao Kato, Naomi Kodama -- Women's Homelessness: International Evidence on Causes, Consequences, Coping and Policies / Guy Johnson, David C. Ribar, Anna Zhu -- Introduction: Women, the Economy, and Economics / Susan L. Averett, Laura M. Argys, Saul D. Hoffman -- Marital Instability in the United States: Trends, Driving Forces, and Implications for Children / Evelyn L. Lehrer, Yeon Jeong Son -- Marriage Markets in Developing Countries / S Anukriti, Shatanjaya Dasgupta -- Fertility Issues and Policy in Developing Countries / t Nonmarital and Teen fertility / Jason M. Fletcher, Jessica Polos -- Child Gender and the Family / Elaina Rose.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on June 5, 2018).
Keywords: Women -- Economic conditions